In work, at home : towards an understanding of homeworking - Felstead, Alan, 1963- (Routledge, 2000)
More and more people are choosing to earn a living at home. In Work, At Home explores the meaning and experience of this type of employment by covering a wide range of issues including:* social relationships* current research methodologies* statistical analyses of global labour markets* the emotional and psychological processes of self-management* home relations. Presenting statistical analyses of labour markets in North America, Europe, Asia and Australia, In Work, At Home provides a valuable introduction to the issues and debates surrounding homeworki.
Keywords: Self-employed -- United States.; Self-employed.; Home labor -- United States.; Home labor.; Home-based businesses -- United States.; Home-based businesses.; Cottage industries -- United States.; Cottage industries.; Travailleurs indépendants -- États-Unis.; Travailleurs indépendants.; Travail à domicile -- États-Unis.; Travail à domicile.; Entreprises établies à domicile -- États-Unis.; Entreprises établies à domicile.; Industrie familiale -- États-Unis.; Industrie familiale.; cottage industries.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Cottage industries; Home-based businesses; Home labor; Self-employed; United States; Heimarbeit; Thuiswerk.; Huisindustrie.; Economische aspecten.; Psychologische aspecten.